The psychosocial burden of hand eczema: Data from a European dermatological multicentre study. (21st February 2018) - Marron, Servando E.; Tomas‐Aragones, Lucia; Navarro‐Lopez, Jorge; Gieler, Uwe; Kupfer, Jörg; Dalgard, Florence J.; Lien, Lars; Finlay, Andrew Y.; Poot, Françoise; Linder, Dennis; Szepietowski, Jacek C.; Misery, Laurent; et al.
Abstract : Background: The essential physical role, visibility and social importance of the hands place a major psychological burden on patients with hand eczema. Objectives: The aim of this study was to identify the psychological, social and clinical characteristics of patients with hand eczema, in particular the prevalences of depression, anxiety, suicidal ideation, and comorbidities. Materials and methods: Data on patients with hand eczema were analysed from a large European multicentre study conducted with dermatology outpatients from 13 countries. Groups of patients and controls were compared to analyse the psychological burden of hand eczema. Results: Female patients with hand eczema had higher Hospital Anxiety and Depression Scale (HADS) scores for anxiety ( n  = 86, median = 7.0) than controls ( n  = 900, median = 5.0, P  = .02), and for depression (median = 4.0) than controls (3.0, P  < .001). Patients with high suicidal ideation, with low socioeconomic status and who were widowed or divorced were more likely to fulfil the HADS criteria for anxiety [odds ratio (OR) > 1, P  = .038, P  < .001, and P  < .001, respectively]. The median Dermatology Life Quality Index score was 7.0 ( n  = 68). Discussion: This study identifies a specific psychological burden experienced by hand eczema patients, highlighting the need for focused psychosocial interventions. Physicians in particular should be aware of the need to identify anxiety and depression in female patients.